1987
DOI: 10.1038/bjc.1987.199
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of multiple primary tumours in patients treated for cancer during childhood

Abstract: Summary One hundred and sixty one children who have developed more than one primary neoplasm have been identified. Children with tumours of the central nervous system, retinoblastoma and leukaemia were those most frequently observed to develop a second malignancy whilst osteosarcoma was the most common second tumour. The patterns of second neoplasms appear to be changing and a recent increase in the number of children with leukaemia and lymphoma who develop second primary tumours has been observed. In this ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 34 publications
0
41
0
2
Order By: Relevance
“…16 Several reports have established a causal relation between the occurrence of multiple malignancies and a genetic syndrome in children with primary brain tumors. 2,3,10,12,13 The relation between NF1 and subsequent neoplasms has been well documented, although the impact of intervening therapies is less well established. A small number of case reports and only two series have demonstrated this relation with respect to syndromes other than NF1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…16 Several reports have established a causal relation between the occurrence of multiple malignancies and a genetic syndrome in children with primary brain tumors. 2,3,10,12,13 The relation between NF1 and subsequent neoplasms has been well documented, although the impact of intervening therapies is less well established. A small number of case reports and only two series have demonstrated this relation with respect to syndromes other than NF1.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of case reports and only two series have demonstrated this relation with respect to syndromes other than NF1. 3,13,[22][23][24] Kingston et al reported that a genetic condition other than NF1 was present in 5 of 45 children (11%) with primary CNS tumors who later experienced an SN; 3 of those patients had Gorlin syndrome, 1 patient had Turcot syndrome, and 1 patient had tuberous sclerosis. 3 In the other series, two patients with Gorlin syndrome were among the four patients overall who developed an SN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the MRI scan did not reveal typical signs of intracranial metastases; therefore, we treated this patient as if the intracranial tumor was a primary glioma, a diagnosis that was confirmed by postoperative pathological results. Although, there are some reports suggesting that intracranial tumors can occur as secondary primary malignancies [4,7,8], the shortest interval between the two malignancies was greater than 12 months [8]. However, the interval in our case was only two months, and the patient did not undergo any radiotherapy or chemotherapy during this period.…”
Section: Discussionmentioning
confidence: 43%